Penyuluhan Kesehatan Reproduksi Pada Remaja Putri Di Desa Nagrak Dan Ciangsana, Bogor - Atut Cicih Mayasari; Raditya Wratsangka; Denny Dhanardono (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Based on demographic data displayed online, the 10-19 age group comprises a significant portion of the total population of Nagrak Village, approximately 20%. In Bogor City, the incidence of stunting among toddlers reaches 24%. This reflects the nutritional status of women in this area. Therefore, anemia is also a key parameter. The number of Community Health Centers (Puskesmas) in Bogor City in 2021 was 1 in 23,756, significantly supporting health education efforts. Counseling is needed to improve the knowledge, attitudes, and behavior of adolescent girls, especially in the villages of Nagrak and Ciangsana, Bogor.